The jungle book - Kipling, Rudyard, 1865-1936; Paolini, Christopher; Langford, Alan (New York : Puffin Books/Penguin Group, 2009)
The adventures of Mowgli, the boy reared by a pack of wolves in an Indian jungle. Includes songs of the animals.
Reprint. Originally published in 1987.
First published 1894.
"Plus a behind-the-scenes journey, including an author profile, a guide to who's who, activities and more..."--P. [4] of cover.
1020
Keywords: Mowgli (Fictitious character) -- Juvenile fiction; Jungle animals -- India -- Juvenile fiction; Feral children -- India -- Juvenile fiction; Jungles -- India -- Juvenile fiction; Mowgli (Fictitious character) -- Fiction; Jungle animals -- India -- Fiction; Feral children -- India -- Fiction; Jungles -- India -- Fiction; Children's stories